Reliable processing of graphene using metal etchmasks - Peltekis Nikos; Lee Kangho; Kim Hye-Young; Kumar Shishir; Duesberg Georg (Nanoscale Research Letters, 2011)
Abstract Graphene exhibits exciting properties which make it an appealing candidate for use in electronic devices. Reliable processes for device fabrication are crucial prerequisites for this. We developed a large area of CVD synthesis and transfer of graphene films. With patterning of these graphene layers using standard photoresist masks, we are able to produce arrays of gated graphene devices with four point contacts. The etching and lift off process poses problems because of delamination and contamination due to polymer residues when using standard resists. We introduce a metal etch mask which minimises these problems. The high quality of graphene is shown by Raman and XPS spectroscopy as well as electrical measurements. The process is of high value for applications, as it improves the processability of graphene using high-throughput lithography and etching techniques.